Cis-trans peptide variations in structurally similar proteins - Joseph, Agnel Praveen (Springer-Verlag, 2012)
The presence of energetically less favourable cis peptides in protein structures has been observed to be strongly associated with its structural integrity and function. Inter-conversion between the cis and trans conformations also has an important role in the folding process. In this study, we analyse the extent of conservation of cis peptides among similar folds. We look at both the amino acid preferences and local structural changes associated with such variations. Nearly 34% of the Xaa-Proline cis bonds are not conserved in structural relatives; Proline also has a high tendency to get replaced by another amino acid in the trans conformer. At both positions bounding the peptide bond, Glycine has a higher tendency to lose the cis conformation. The cis conformation of more than 30% of β turns of type VIb and IV are not found to be conserved in similar structures. A different view using Protein Block based description of backbone conformation, suggests that many of the local conformational changes are highly different from the general local structural variations observed among structurally similar proteins. Changes between cis and trans conformations are found to be associated with the evolution of new functions facilitated by local structural changes. This is most frequent in enzymes where new calalytic activity emerges with local changes in the active site. Cis-trans changes are also seen to facilitate inter-domain and inter-protein interactions. As in the case of folding, cis-trans conversions have been used as an important driving factor in evolution.